2022
DOI: 10.1021/jacs.2c05421
|View full text |Cite
|
Sign up to set email alerts
|

{ScnGdn} Heterometallic Rings: Tunable Ring Topology for Spin-Wave Excitations

Abstract: Data carriers using spin waves in spintronic and magnonic logic devices offer operation at low power consumption and free of Joule heating yet requiring noncollinear spin structures of small sizes. Heterometallic rings can provide such an opportunity due to the controlled spin-wave transmission within such a confined space. Here, we present a series of {Sc n Gd n } (n = 4, 6, 8) heterometallic rings, which are the first Sc–Ln clusters to date, with tunable magnetic interactions for spin-wave excitations. By me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Usually, higher α and β values and lower OL values are key parameters for considering optical limiting performance. These values are not as good as those of some porphyrins and phthalocyanine materials, such as 2,9(10),16 (17),23(24)-tetrakis-(4-pyridyloxy) phthalocyaninato (H 2 TPPc) with detonation nanodiamonds in DMSO and single-walled carbon nanotube-5,10,15,20-tetraphenylporphyrin (SWN 7 -TPP) in DMF, but superior to those of some known transition metal cluster materials, which include but are not limited to, KBr-based AgSn 12 cluster thin films, graphene oxide (GO) in DMF and [(Tp*WS 3 Cu 3 ) 4 (μ 4 -S) 4 (Ag)]OTf (3@PVBC) thin films (Fig. 4e and Table S9 †).…”
Section: Third-order Nonlinear Optical (Nlo) Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Usually, higher α and β values and lower OL values are key parameters for considering optical limiting performance. These values are not as good as those of some porphyrins and phthalocyanine materials, such as 2,9(10),16 (17),23(24)-tetrakis-(4-pyridyloxy) phthalocyaninato (H 2 TPPc) with detonation nanodiamonds in DMSO and single-walled carbon nanotube-5,10,15,20-tetraphenylporphyrin (SWN 7 -TPP) in DMF, but superior to those of some known transition metal cluster materials, which include but are not limited to, KBr-based AgSn 12 cluster thin films, graphene oxide (GO) in DMF and [(Tp*WS 3 Cu 3 ) 4 (μ 4 -S) 4 (Ag)]OTf (3@PVBC) thin films (Fig. 4e and Table S9 †).…”
Section: Third-order Nonlinear Optical (Nlo) Propertiesmentioning
confidence: 83%
“…[13][14][15] Furthermore, heterometallic 3d-4f molecular rings are also the stars of hybrid molecular rings, such as Cr 4 Dy 4 , Sc 8 Gd 8 , and Mo 128 Ce 4 with modified delta-chain structures, which are linked via benzoates. [16][17][18] These macrocyclic molecules exhibit distinct benefits in the optics, magnetism and host-guest chemistry domains. [19][20][21][22][23] Yang et al reported a {Nd 18 } molecular ring exhibiting NIR luminescence sensing of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…They not only exhibit fascinating topologies but also have unique properties that differrent from individual metal ions and lanthanide nanomaterials due to the synergistic and/or coupling interactions within the metal ions [7][8][9][10][11][12]. The outstanding advantage of metal clusters is their definite atomic composition and the well-defined geometrical structure, which can be modulated by changing the internal atoms and surface ligands [13][14][15][16][17]. Considerable efforts in this field have resulted in the fabrication of a large number of LnOCs based on organic ligands [18][19][20][21][22][23].…”
Section: Instructionmentioning
confidence: 99%
“…[8][9][10][11] In recent years, great progress has been made in mononuclear dysprosium complex based single-molecule magnets (SMMs) with a large flip energy barrier (U eff ) and high hysteresis temperature (T B ). [12][13][14][15][16][17][18] Mononuclear dysprosium complexes may represent the lower size limit of molecule based magnetic information storage materials, which may mean that high-nucleation dysprosium clusters can comprise SMMs with better performance. Therefore, high-nuclear dysprosium based SMMs will be a more promising direction in the field of molecular magnetism in the future.…”
Section: Introductionmentioning
confidence: 99%